Epidemiologija urinske inkontinence pri ženskah - But, Igor (Medicinski razgledi, 2005)
Urinary incontinence is a highly prevalent condition that can represent a significant emotional, social and psychological burden for the affected woman. It is one of the most common health problems in women, especially the elderly. Costs of diagnosis and therapy burdening health care systems are within the range of those for diabetes or hypertension in most Western countries. Yet, relatively little is known about the epidemiology and natural history of female urinary incontinence. Some new knowledge about this disturbance is reviewed in the article.
Keywords: Urinary incontinence; Urinska inkontinenca; Epidemiologija; Epidemiology; Incidence; Prevalenca; Prevalence; woman; Ženske; Incidenca; Women